HUBUNGAN PENGETAHUAN GIZI IBU DENGAN KEJADIAN STUNTING PADA ANAK BALITA DI DESA BUHU KECAMATAN TALAGA JAYA KABUPATEN GORONTALO - Salman Lukman; Fitri Yani Arbie; Yulin Humolungo (Jurusan Gizi Politeknik Kesehatan Gorontalo, 2017)
Stunting is a state where the body is very short to exceed -2 standard deviation (SD) under long or high lengths that becomes an international reference. Stunting describes a state of under-nutrition that has been running for a long time and requires time for the child to grow and recover (Gibney et al., 2013). This study aims to determine the relationship of mothers’ nutritional knowledge with the incidence of stunting in children under five in Buhu Village Talaga Jaya District, Gorontalo District. Methods: analytical survey research with cross-sectional study design. Population:135 infants and 57 toddlers were obtained by using Proportional random sampling. The independent variable is mothers’ nutrition knowledge and the dependent variable is stunting incident in the toddler. Data analysis: statistical test